Engineering research for self-reliance-modeling and simulation perspective (2009)
"Engineering research is a sine-qua-non for development of new products, new production processes, hence production lines in the quest for self reliance in any economy. Modeling and simulation is a veritable tool for such research and development. This paper presents the multifaceted use of modeling and simulation as decision tools for engineering facet of an economy drawing examples from two different engineering disciplines- Metallurgical and Civil. "